2013
DOI: 10.1016/j.pscychresns.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in global and local level information processing in autism: An fMRI investigation

Abstract: People with autism spectrum disorders (ASD) have atypical visual perception of global and local information. Previous neuroimaging studies have examined the functional anatomy of locally-directed attention during visual processing in ASD, but few have examined differences in both globally-and locally-directed attention. We performed functional magnetic resonance imaging (fMRI) in 17 adults with ASD and 16 typically developing (TD) subjects to examine the neurobiology of both global- and local- level informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…In autism spectrum disorders, a prototypical developmental disorder, sensory perception is often reported to be atypical. In particular, autistic participants display poor global form processing in some studies (Happé, 1996; Happé & Frith, 2006; Plaisted et al, 1999), although the existence of global perceptual deficits in autism is still open to debate (e.g., Rondan & Deruelle, 2007; Milne & Scope, 2008; Gadgil et al, 2013; Bernardino et al, 2012; Hayward et al, 2012). Establishing a developmental profile for global form processing using an objective approach like ours may provide insights into differences between perceptual skills of developmentally challenged children and those who are typically developing, as well as provide clues into the neural mechanisms involved in KIC perception.…”
Section: Discussionmentioning
confidence: 99%
“…In autism spectrum disorders, a prototypical developmental disorder, sensory perception is often reported to be atypical. In particular, autistic participants display poor global form processing in some studies (Happé, 1996; Happé & Frith, 2006; Plaisted et al, 1999), although the existence of global perceptual deficits in autism is still open to debate (e.g., Rondan & Deruelle, 2007; Milne & Scope, 2008; Gadgil et al, 2013; Bernardino et al, 2012; Hayward et al, 2012). Establishing a developmental profile for global form processing using an objective approach like ours may provide insights into differences between perceptual skills of developmentally challenged children and those who are typically developing, as well as provide clues into the neural mechanisms involved in KIC perception.…”
Section: Discussionmentioning
confidence: 99%
“…This view raises a possibility that such preference in ASD might be linked with atypical brain activity in brain regions related to visual information processing and its control. Indeed, previous fMRI studies have demonstrated that the SFG is critically involved in visuospatial attention and visual spatial working memory [ 63 66 ], and that individuals with ASD show atypical activation in the SFG while attending to local patterns in the hierarchical shape-recognition task [ 67 ]. Considering these findings, our results may suggest a possibility that local over-connectivity in the right SFG and MFG might be related to atypical visual information processing in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…A functional MRI study of sustained attention in autism conducted by Christakou et al (2013) found that individuals with autism had significantly reduced activation relative to healthy controls (but similar activation to an ADHD sample) in the bilateral striato-thalamic regions, left dorsolateral prefrontal cortex (DLPFC), and superior parietal cortex. However, ASD individuals displayed increased precuneus activation, which was negatively correlated with DLPFC activation and became more pronounced with increased attentional demands (see also, Gadgil, Peterson, Tregellas, Hepburn, & Rojas, 2013). Overall, the literature suggests distinct attentional patterns for individuals with autism likely differ from those with typical development.…”
Section: Attention-related Structural and Functional Patterns And Autismmentioning
confidence: 97%